Mechanical Thrombectomy for Tandem Occlusions of the Internal Carotid Artery—Results of a Conservative Approach for the Extracranial Lesion - Blassiau, Alexandre; Gawlitza, Matthias; Manceau, Pierre-François; Bakchine, Serge; Serre, Isabelle; Soize, Sébastien; Pierot, Laurent (Frontiers in Neurology, 2018)
Background: Mechanical thrombectomy (MT) is of clinical benefit for patients with extracranial-intracranial tandem lesions of anterior circulation. However, the optimal approach to the cervical lesion of the internal carotid artery (ICA) during MT has yet to be established. Data on a conservative approach for the proximal lesion during the acute phase are scarce. Methods: A retrospective study on an institutional, prospective database was conducted. We included patients with anterior circulation stroke presenting with a tandem lesion that was approached conservatively during MT. Results: 35 patients were included, of whom 25 (71.4%) had an atheromatous ICA lesion and 10 (28.6%) a dissection. Despite implementing a conservative strategy, acute percutaneous transluminal angioplasty (PTA) and/or stenting was necessary in 8 (22.9%) and 3 patients (8.6%), respectively. Of 27 surviving patients, 7 (25.9%) underwent delayed treatment of the ICA lesion. No new embolic events occurred between MT and delayed treatment. A favorable clinical outcome (mRS≤2) was achieved in 15/35 patients (45.7%) and was associated with higher baseline ASPECTS (OR 1.62, 95% CI 1.08-2.45, p=0.002) and successful recanalization (OR 9.39, 95% CI 1.92-45.80, p=0.0005). Successful recanalization (TICI ≥2B) itself was observed in 54.3% of patients and was more likely with acute treatment of the proximal ICA lesion (OR 6.3, 95% CI 11-35.67, p=0.03) and, more importantly, by the use of distal access catheters (OR 16.25, 95% CI 3.06-86.41, p=0.0001). Conclusion: A conservative approach for ICA lesions during MT is feasible and offers favorable outcomes and successful recanalization for a significant proportion of patients. However, acute treatment of the cervical lesion is often necessary (31.4%) to make the distal occlusion accessible. Clinical outcome is influenced by the size of the baseline ischemic core and by successful recanalization; the latter is strongly favored by the use of distal access catheters to pass the proximal lesion. The fact that acute treatment of the ICA lesion favored intracranial recanalization but had no effect on clinical outcome is probably due to sample size, emphasizing the need for large scale, randomized studies to determine the optimal treatment strategy for this pathology.